A Comparative Study on Image Segmentation Techniques - Kaur, Balpreet; Kaur, Prabhpreet (International Journal of Computer Sciences and Engineering, 2025)
Image segmentation is the first step from image processing to image analysis. Image segmentation is the partition of image into multiple segments to have clear distinction between object and background of image. In existing method, in order to obtain threshold accurately, discrete wavelet transform (DWT) method is used which decompose the image into four sub-bands via high and low pass filters. To determine threshold value, Otsu’s method is applied on low pass filter and on high pass filter edge enhancement is implemented. The overall objective of this paper is to review the image segmentation techniques and find their limitations.